Imaging temporomandibular disorders: Reliability of a novel MRI-based scoring system - Willenbrock, Dorina; Lutz, Rainer; Wüst, Wolfgang; Heiß, Rafael; Uder, Michael; Behrends, Tessa; Wurm, Matthias; Kesting, Marco Rainer; Wiesmüller, Marco (Journal of Cranio-Maxillofacial Surgery, 2022)
The aim of this study was to assess the inter- and intrarater reliability of a recently proposed scoring system for temporomandibular disorders (TMD), based upon radiological findings from magnetic resonance imaging (MRI). Patients with clinically suspected uni- or bilateral TMD, and subsequently conducted MRI examination of both temporomandibular joints, were included in this study. MRI data were independently evaluated by two experienced radiologists according to the DLJ scoring system proposed by Wurm et al., which includes assessment of the following categories: articular disk (prefix ‘D’), direction of disk luxation (prefix ‘L’), and osseous joint alterations (prefix ‘J’). 60 patients (49 female and 11 male) were eligible for analysis. No significant differences were found between both observers regarding ‘D’ and ‘L’ scores (p = 0.13 and p = 0.59, respectively). Significant differences were found for the assessment of subtle osseous changes (‘J0’ category: p = 0.041; ‘J1’ category: p = 0.018). Almost perfect intra- and interrater agreements were found for ‘D’ and ‘L’ categories (intrarater and interrater agreements for ‘D’: κ = 0.92 and κ = 0.84, respectively; intrarater and interrater agreements for ‘L’: κ = 0.93 and κ = 0.89, respectively). However, the assessment of ‘J’ categories revealed only moderate interrater agreement (κ = 0.49). The DLJ scoring system based upon MRI findings is feasible for routine clinical TMD assessment, and may help to simplify interdisciplinary communication between radiologists and clinicians.
CRIS-Team Scopus Importer:2022-04-08
Keywords: DLJ score; Magnetic resonance imaging; MRI; Temporomandibular disorder; TMD